PENGARUH LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN ( Studi kasus pada karyawan bagian Departemen Finishing di PT.Riau Andalan Kertas Kab.Pelalawan Provinsi Riau ) - Bernad Harianja; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Work environment is everything that is around an employee of a company. The work environment should be considered by the management, as it will affect the job satisfaction of employees. With improvements in the work environment will be able to increase job satisfaction and indirectly improve performance and ultimately will be able to facilitate the company achieve its goals in accordance with the plans that have been prepared well. Job satisfaction is a pleasant emotional attitude and loves his job. This attitude is reflected by the morale, discipline and performance.The purpose of this study was to determine whether the work environment have a significant effect on job satisfaction of employees at PT. Riau Andalan Kertas. This research was conducted by taking a sample of 72 respondents. Data were collected using a questionnaire in the form of a list of statements. The data analysis technique used is multiple linear regression using SPSS 20.0 for Windows.The results showed that simultaneously working environment have a significant effect on employee job satisfaction PT. Riau Andalan Kertas, This means that the working environment can improve employee job satisfaction PT. Riau Andalan Kertas.Keywords: work environment ,the non physical work environment, job satisfaction.